Marriage Agreement As Legal Protection For Both Parties in Marriage - Kresna Ayung Begawan; I Ketut Kasta Arya Wijaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the marriage agreement as an instrument of legal protection for both parties in a marriage, especially in terms of property ownership and financial responsibility. This study uses a sociological juridical method, with primary data obtained through interviews with a notary and secondary data from various legal literature, including Law Number 1 of 1974 concerning Marriage, the Civil Code, and the Constitutional Court Decision Number 69/PUU-XIII/2015. The results of the study indicate that the marriage agreement plays a role in preventing potential legal conflicts in marriage, both in monogamous and polygamous systems, and provides legal certainty for third parties, such as creditors or heirs. This agreement not only protects the rights and obligations of the husband and wife, but also ensures legal clarity in the division of assets and financial responsibility during and after the marriage.